Analisis Daya Saing Komparatif Komoditas Kopi (Coffea Sp.) Indonesia di Pasar Internasional - Sabrina Tasya; Suhaeni Suhaeni; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Coffee is one of Indonesia's mainstay commodities. Indonesia is the world's fifth largest coffee exporter for 2020, but within 10 years the export value and production of Indonesian coffee commodities have not been superior to their competitors, namely Brazil, Honduras, Colombia and Vietnam. The purpose of this study is to analyze the comparative competitiveness of Indonesian coffee in the international market. This study uses a quantitative descriptive method. The analytical method used to measure the comparative competitiveness of a country's commodities is Revealed Comparative Advantage (RCA) analysis. The results of the study indicate that Indonesian coffee commodities have strong competitiveness (RCA> 1), but the average RCA is lower than Brazil, Honduras, Colombia and Vietnam.